2011
DOI: 10.1007/s00477-011-0530-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the properties of the relationship between rare and extreme rainfall and flood volumes, under some distributional restrictions

Abstract: The fact that rainfall data are usually more abundant and more readily regionalized than streamflow data has motivated hydrologists to conceive methods that incorporate the hydrometeorologial information into flood frequency analyses. Some of them, particularly those derived from the French GRADEX method, involve assumptions concerning the relationship between extreme rainfall and flood volumes, under some distributional restrictions. In particular, for rainfall probability distributions exhibiting exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…He suggested that for very large return period floods, for example, beyond 500 years, the distribution of the maximum mean rainfall intensity over a duration in the order of the time of concentration of the catchment should be considered as the possible flood peak asymptotic distribution, as schematically illustrated in Figure 5. The suggestion that the flood tail heaviness follows the tail heaviness of precipitation for large return periods is also the basic assumption of the GRADEX method which is widely used in practice, particularly in France (Naghettini et al., 2012). The return period beyond which the flood distribution follows the rainfall distribution is typically set to much lower values, for instance, to 10–20 years for relatively impermeable watersheds and up to 50 years for watersheds with high infiltration capacity (Naghettini et al., 2012).…”
Section: Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…He suggested that for very large return period floods, for example, beyond 500 years, the distribution of the maximum mean rainfall intensity over a duration in the order of the time of concentration of the catchment should be considered as the possible flood peak asymptotic distribution, as schematically illustrated in Figure 5. The suggestion that the flood tail heaviness follows the tail heaviness of precipitation for large return periods is also the basic assumption of the GRADEX method which is widely used in practice, particularly in France (Naghettini et al., 2012). The return period beyond which the flood distribution follows the rainfall distribution is typically set to much lower values, for instance, to 10–20 years for relatively impermeable watersheds and up to 50 years for watersheds with high infiltration capacity (Naghettini et al., 2012).…”
Section: Atmospherementioning
confidence: 99%
“…The suggestion that the flood tail heaviness follows the tail heaviness of precipitation for large return periods is also the basic assumption of the GRADEX method which is widely used in practice, particularly in France (Naghettini et al., 2012). The return period beyond which the flood distribution follows the rainfall distribution is typically set to much lower values, for instance, to 10–20 years for relatively impermeable watersheds and up to 50 years for watersheds with high infiltration capacity (Naghettini et al., 2012). Such low values are in contrast to McCuen and Smith (2008) and Gaume (2006) who suggested that the tail behavior of the flood distribution was inherited from the rainfall distribution in the extreme case only, that is, for very large return periods.…”
Section: Atmospherementioning
confidence: 99%
“…While we cannot directly transfer the GEV shape parameter from rainfall to flood peak distributions, rainfall still has an important role: in his analytical analysis, Gaume (2006) states that "the shape of the flood peak distribution is asymptotically controlled by the rainfall statistical properties, given limited and reasonable assumptions concerning the rainfall-runoff process". A similar assumption is the basis of the GRADEX method which is used in practice, for example, in France (Naghettini et al, 2012). The method assumes that beyond a certain return period, the upper tail of a flood peak distribution is the same as the upper tail of the rainfall distribution (Naghettini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A similar assumption is the basis of the GRADEX method which is used in practice, for example, in France (Naghettini et al, 2012). The method assumes that beyond a certain return period, the upper tail of a flood peak distribution is the same as the upper tail of the rainfall distribution (Naghettini et al, 2012). While in the GRADEX method, this return period is usually assumed to be between 10 and 50 years (Naghettini et al, 2012), Gaume (2006) estimates it to be beyond 500 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation